2005
DOI: 10.1089/neu.2005.22.1052
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Pentose Phosphate Pathway and Preservation of Tricarboxylic Acid Cycle Flux after Experimental Brain Injury

Abstract: The metabolic fate of [1,2 13C]-labeled glucose was determined in male control and unilateral controlled cortical impact (CCI) injured rats at 3.5 and 24 h after surgery. The concentration of 13C-labeled glucose, lactate, glutamate and glutamine were measured in the injured and contralateral cortex. CCI animals showed a 145% increase in 13C lactate in the injured cortex at 3.5 h, but not at 24 h after injury, indicating increased glycolysis in neurons and/or astrocytes ipsilateral to CCI. Total levels of 13C g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
117
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(135 citation statements)
references
References 86 publications
15
117
3
Order By: Relevance
“…In fact it was at levels comparable to those reported after stress such as traumatic brain injury in adult human and rodent brain [24,25]. Activity of the PPP was evident in neurons due to the presence of [4-C]glutamate.…”
Section: Pppsupporting
confidence: 78%
See 1 more Smart Citation
“…In fact it was at levels comparable to those reported after stress such as traumatic brain injury in adult human and rodent brain [24,25]. Activity of the PPP was evident in neurons due to the presence of [4-C]glutamate.…”
Section: Pppsupporting
confidence: 78%
“…These needs can be met by the PPP, which produces nucleotides and NADPH. Earlier studies have shown that the pathway accounts for approximately 2-5 % [21][22][23] of the glucose metabolism in the adult brain and can be upregulated to 9-20 % in response to injury in animal and human studies [24,25]. However, little is known about the PPP in the developing brain.…”
mentioning
confidence: 99%
“…An appropriate comparison for our study used adult monkey brains and found PPC activity of 5.6% in the cerebral hemispheres, 5.4% in brainstem, 6.4% in hypothalamus, and 8% in cerebellum (Hostetler et al, 1970). Recent studies from our laboratory of brain tissue extracts in a rat brain injury model confirm the increase in PPC flux after TBI (Bartnik et al, 2005).…”
Section: Normal Cerebral Pentose Phosphate Flux and Increased Flux Afsupporting
confidence: 51%
“…36) In previous study, the pentose phosphate pathway is increased after traumatic brain injury. 37) These suggested that increase of 6-phosphogluconolactonase may contribute to enhance of anti-oxidative stress after cerebral ischemia. Apoprotein A-I, which the major component antiatherogenic properties of high density lipoprotein (HDL) are mainly related to reverse cholesterol transport process (i.e., removing excess cholesterol from the arterial wall's foam macrophages to the liver for metabolism).…”
Section: Discussionmentioning
confidence: 99%